New Media and Cultural Strengthening in Exploring Old Tombs, Heritage of East Sumatran Civilization - Datuk Imam Marzuki (Britain International for Academic Research (BIAR) Publisher, 2024)
The old tombs left by the Malay kingdom of East Sumatra are an interesting study. In a historical context, it is part of the heritage in the form of artifacts with distinctive tombstone motifs. In parts of the world, the culture of visiting old graves is often called pilgrimage tourism or popularly called the rihlah of civilization. Several Islamic countries routinely carry out this, such as Iran, Pakistan, Türkiye and Sudan. Apart from the tourism aspect, this activity also contains spiritual and religious elements. The existence of old graves can be accessed easily due to information spread on YouTube media. It also helps when searching for these places and locations when using Google Maps. Using smartphone media technology, such as smartphone applications, can increase the involvement of the younger generation in learning history.